Potato yield and nutrient acquisition are supported by the soil "bacteriome" - Barnett, Brittany Allison, author; Manter, Daniel K., advisor; Bunning, Marisa L., committee member; Holm, David G., committee member; Vivanco, Jorge M., committee member; Weir, Tiffany L., committee member (Colorado State University. Libraries, 2013)
Potatoes are the fourth largest food crop in the world; they are a staple food for much of South America and are the most consumed vegetable per capita in the United States. Breeding programs across the country seek to produce cultivars that are high yielding, disease resistant, and nutritious. The plant-soil-microbial community is greatly intertwined, each piece affecting the others. Soil microbial communities are highly influenced by edaphic features, and within a site microbial communities are influenced by the specific potato clone. The first section of this project (Chapter 2) illustrates the variability in the bacterial root-associated community due to site and clone. The underlying core bacterial community of combined potato roots/rhizosphere soil that might benefit the quality of the potato crop was also examined. Root/rhizosphere soils from 18 different clones along with bulk soil bacterial communities from three sites (CA, CO, TX) were examined using 454 sequencing. In order to explain the soil bacterial potential, SPLS regression techniques were used to identify root-associated microbes correlated with tuber yield. Twenty-two bacterial operational taxonomic units (OTUs) were found to have a significant positive relationship with potato yield, many of these belonging to the bacterial order Rhizobiales. Interestingly, many of the bacteria identified in the SPLS regression have been studied in agricultural systems, however rarely in relation to potato. Further study of the relationship between potato plants and these microbes is warranted. Parts of South America, where potato is a staple food, have been described as good candidates for the implementation of biofortified foods; additionally, the potato is a good candidate for biofortification. Biofortification of foods through plant breeding can increase essential nutrients in staple crops to decrease human disease and mortality. The second aspect of this project (Chapter 3) assessed the impact that soil nutrient contents, soil bacterial diversity, and potato clones have on tuber nutrient contents. A predictive model was created to address the degree to which these independent predictors impact the tuber nutrient levels of N, P, K, Zn, Fe, Mn and Cu. Soil nutrient levels and bulk soil bacterial diversity had a similar ability to increase tuber nutrient levels. Increasing soil bacterial diversity was shown to support acquisition of these seven nutrients. This indicates that management practices to increase soil bacterial diversity may support plant nutrient acquisition, thus lowering fertilizer use.
Keywords: model; soil; bacteria; core; mineral; nutrient